Gastrochilus pseudocalceolaris, a new species of epiphytic orchid from India - Dey, Santanu; Phom, Limamanen; Avishek Bhattacharjee; Moaakum; Eshuo, Kazhuhrii (Phytotaxa, 2022)
The article deals with description of a new species of epiphytic orchid, viz. Gastrochilus pseudocalceolaris S. Dey, L. Phom, Av. Bhattacharjee, Moaakum & K. Eshuo, along with detailed description, photographs, photo-plates, and taxonomic note. The new species, collected from Mt. Yingyushang, Longleng district, Nagaland in India, is morphologically most similar to Gastrochilus calceolaris (Buch.-Ham. ex Sm.) D. Don, but differs in having much shorter stem and features of labellum. The types have been stored to CAL for future reference.